Organophosphate pesticide exposure among farm women and children: Status of micronutrients, acetylcholinesterase activity, and oxidative stress. Issue 2 (7th February 2022) - Medithi, Srujana; Kasa, Yogeswar Dayal; Jee, Babban; Kodali, Venkaiah; Jonnalagadda, Padmaja R.
Abstract: Nutritional status plays a major role in determining the possible adverse health outcomes due to pesticide toxicity. The objective of the present study was to assess the organophosphorus pesticide residue levels among farm women (FW) (24-45years) and farm children (FC) (9-12 and 13-15years) belonging to the Rangareddy district (Telangana, India) along with their micronutrient status, inhibition of acetylcholinesterase activity, and oxidative stress levels. Residues of Chlorpyrifos, Diazinon, Malathion, Monocrotophos and Phosalone were found in the serum samples of FW and FC along with significantly low levels of vitamins and minerals. Inhibition of AChE activity was observed in FW and FC and altered oxidative stress parameters among FW. Correlation studies have found significant associations between the pesticide residues, micronutrients and antioxidant enzymes. The study suggests an association between pesticide exposure coupled with micronutrient deficiency, induced AChE inhibition, and oxidative stress.